PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENS TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SEKOLAH DASAR NEGERI 161 PEKANBARU - Sari, Epi Manda; Noviana, Eddy; Lazim N, Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to improve social science outcomes with Student Teams Achievement Division (STAD) for student of V SDN 161 Pekanbaru. The result of research showed that social science through Student Teams Achievement Division can improve social science outcomes.This study is classroom action research (CAR). This can be seen from : (1) teacher activity increases from percentages of teacher activity in the first cycle of 62,5 %( enough category), in the second cycles of 91,66% (very good category); (2) student learning activities of increase in each cycle, this can be seen from the percentage of student learning activities in the first cycle of 62,5% (enough category), and increased in the second cycle of 87,5% (very good category); (3) student learning outcomes increase from avarage basic value 57,33 with completness 33,33% (unfinished), and then increase in the first cycle equal to 29,94% with a value 74,50, and in the second cycle increased by 47,39%with value 84,5. And then, the conclusion is the application of cooperative learning model of student teams achievement division (STAD) can improve learning outcomes on social science of fifth grade students of SD Negeri 161 Pekanbaru.Keywords : Student teams Achievement Division (STAD), learning outcomes, Classroom Action Research (CAR